Portomesenteric Vein Thrombosis, Bowel Gangrene, and Bilateral Pulmonary Artery Embolism Two Weeks after Laparoscopic Sleeve Gastrectomy - David G. Darcy; Ali H. Charafeddine; Jenny Choi; Diego Camacho (Case Reports in Surgery)
Sleeve gastrectomy and gastric bypass surgery are popular and effective options for weight loss surgery. Portomesenteric vein thrombosis (PMVT) is a documented but rare complication of bariatric surgery. Proper surgical technique, careful postoperative prophylaxis, and early mobilization are essential to prevent this event. The diagnosis of PMVT in the postoperative period requires a high index of suspicion and early directed intervention to prevent a possibly fatal outcome. We present a case of PMVT complicated by small bowel ischemia resulting in gangrene that necessitated resection.